Penggunaan Media Beruang Antik Berbasis STEAM pada Materi Bangun Ruang Siswa Kelas VI SD Negeri Banggle 02 - Khoir, Ani Kholifatul (SCAD Independent, 2025)
The Covid-19 pandemic outbreak that is currently becoming pandemic in Indonesia is strongly influential in all aspects, one of them is in the education. The world of education gets tremendous impact, particularly for teachers in the learning process, so that learning remains fun even though studying at home. So that teachers have big responsibility to make learning tools as solutions and innovations through the use of various learning tools and online applications. And the Beruang Antik STEAM-based learning media which includes the disciplines of Science, Technology, Engineering, Art and Mathematics students are built to think critically by learning to solve problems using technological tools and creative learning strategies. Beruang Antik Media can assist students to improve creative thinking skills and communication skills. In the implementation of learning, the Beruang Antik media empowers parental involvement, to direct students to solve problems, encourage students to explore, and find new ways. The parental involvement will make online learning using this Beruang Antik Media run optimally.